The prince of spies - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Hope and glory, 2021)
"Luke Delacroix's hidden past as a spy has him carrying out an ambitious agenda-thwarting the reelection of his only real enemy. But trouble begins when he falls for Marianne Magruder, the congressman's daughter. Can their newfound love survive a political firestorm, or will three generations of family rivalry drive them apart forever?"--Provided by publisher.